Development and validation of a real-time PCR assay for the detection of Toxoplasma gondii DNA in animal and meat samples. (March 2017) - Marino, Anna Maria Fausta; Percipalle, Maurizio; Giunta, Renato Paolo; Salvaggio, Antonio; Caracappa, Giulia; Alfonzetti, Tiziana; Aparo, Alessandra; Reale, Stefano
We report a rapid and reliable method for the detection of Toxoplasma gondii in meat and animal tissues based on real-time polymerase chain reaction (PCR). Samples were collected from cattle, small ruminants, horses, and pigs raised or imported into Sicily, Italy. All DNA preparations were assayed by real-time PCR tests targeted to a 98-bp long fragment in the AF 529-bp repeat element and to the B1 gene using specific primers. Diagnostic sensitivity (100%), diagnostic specificity (100%), limit of detection (0.01 pg), efficiency (92–109%), and precision (mean coefficient of variation = 0.60%), repeatability (100%), reproducibility (100%), and robustness were evaluated using 240 DNA extracted samples (120 positives and 120 negative as per the OIE nested PCR method) from different matrices. Positive results were confirmed by the repetition of both real-time and nested PCR assays. Our study demonstrates the viability of a reliable, rapid, and specific real-time PCR on a large scale to monitor contamination with Toxoplasma cysts in meat and animal specimens. This validated method can be used for postmortem detection in domestic and wild animals and for food safety purposes.